Socio-philosophical aspects of M. Heidegger fundamental ontology (Zien Journal of Social Sciences and Humanities, 2023)
proposing a unified theoretical and methodological framework based on revealing the sociophilosophical aspects of Heidegger's "fundamental ontology", which makes it possible to use the possibilities of the doctrine in solving modern problems of social philosophy.